Development of Liposomes That Target Axon Terminals Encapsulating Berberine in Cultured Primary Neurons - Ikuma Hori; Hideyoshi Harashima; Yuma Yamada (MDPI AG, 2023)
Most of the energy in neurons is produced in mitochondria. Mitochondria generate the ATP that is essential for neuronal growth, function, and regeneration. Mitochondrial axonal transport plays a crucial role in maintaining neuronal homeostasis and biological activity. Decreased mitochondrial axonal transport at axon terminals, where the metabolism of substances is likely to be delayed, may contribute to neurological dysfunction. Therefore, regulation of mitochondrial dynamics at axon terminals has attracted considerable interest as a strategy to modulate neuronal function. Nanoparticles may be useful in controlling local mitochondrial dynamics. Nevertheless, there are few reports on the influence of drug delivery that nanoparticles impart on the mitochondrial dynamics in neurons. This paper reports the results of a study using liposomes (LPs) to examine local drug delivery and pharmacological actions on neurons. We tested berberine (BBR), which is an activator of AMP-activated protein kinase (AMPK), to examine the utility of this drug as a cellular energy sensor. Axon terminals targeting LPs were prepared. The amount of axon terminals targeting LPs was increased compared with treatment using cationic LPs. Moreover, axon terminal-targeting LPs increased anterograde transport by about 40% compared with that of either naked BBR or cationic LPs and suppressed axonal retraction. Our findings suggest that local drug delivery to neurons is important for enhancing pharmacological activity in axon terminals.